Assessment of subsurface temperature distribution from the gauged wells of Puga Valley, Ladakh - Shibani K. Jha; Harish Puppala (Geothermal Energy, 2017)
Abstract Among the distinguished zones of geothermal potential in India, the Puga Valley is identified as one of the potential sites for tapping geothermal energy at industrial scale. The hydrogeological properties and the temperature variations with depth have been examined under the Geological Society of India by drilling borewells at a few locations. The temperature distribution is one of the most essential parameters in quantifying the energy potential of a geothermal reservoir in its life time. Such temperature distribution has not been mapped for the Puga Valley. 2D Kriging technique is adopted in this study to assess temperature distribution for thermal manifestation zone at various depths and these are further used to estimate the thermal gradients at ungauged locations of the valley. From the results obtained, it is observed that the thermal gradient in the eastern zone of the valley is relatively higher. This indicates a possible bottom heat source in the eastern zone of the valley. The results of this study could be helpful in identifying the distinctive conceivable locations of injection and production wells for the extraction of entrapped heat within the rock strata. Also, a priority order is drawn in terms of thermal gradients at gauged and ungauged locations which may be helpful in deciding the zones of high and low heat sources in the reservoir.